Zoo Malaya: Aplikasi Pembelajaran Mudah Alih Sains Sekolah Rendah bagi Topik Haiwan Menggunakan Teknologi Realiti Terimbuh - Amir, Muhammad Arif; Senan, Norhalina (Applied Information Technology And Computer Science, 2024)
In today’s era, mobile learning application themed on subject of Science primary schools in Malaysia have been widely developed. However, mobile learning application for the topic of Animals and equipped with Augmented Reality (AR) technology are still less of a focus for companies out there to develop such applications. Therefore, this project has developed a mobile learning application that focuses on the topic of Animals with help of AR technology. The purpose of this project is to help the primary shcool students and teachers use the mobile application to display images related to the animals with AR technology and help students to understand the contuinity between the selected Animals topics. The methodology used in this project is Multimedia Mobile Content Development (MMCD). This application has been developed has been developed on Unity software version 2022 along with the coding process using C# programming language. The results of this project were tested with the subject matter expert (SME) and the target users, where the results of user acceptance of this application were evaluated using the System Usability Scale (SUS) method which showed an excellent average score of 91.625.